RELATIONSHIPS BETWEEN PETROGRAPHIC AND PHYSICOMECHANICAL PROPERTIES OF BASIC IGNEOUS ROCKS FROM THE PINDOS OPHIOLITIC COMPLEX, NW GREECE - Pomonis, P.; Rigopoulos, I.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2007)
The relationships between pétrographie and physicomechanical properties of basic igneous rocks· from the Pindos ophiolitic complex, northwestern Greece, were investigated. The mineralogical composition was quantified from one polished thin section per sample with a polarizing microscope, by using the point count method. Textural description was also carried out by using both polarizing and scanning electron microscope. The same samples were also tested to determine moisture content, water absorption, specific gravity, total porosity, void ratio, uniaxial compressive strength, Los Angeles, micro-Deval, PSV and Sand Equivalent values. The relationships between these properties and the pétrographie characteristics are described by simple regression analyses. The results indicate that plagioclase, chlorite, quartz and actinolite contents of the studied rock-types significantly influence their physicomechanical properties. Additionally, some textural parameters such as the mean grain size and the complexity of grain boundaries influence their mechanical strength.